Pegaruh Penggunaan Media Pembelajaran Berbasis Kahoot Terhadap Hasil Belajar Siswa Kelas X SMK Muhammadiyah 2 Kuningan - Sya’bani, Wildan Nur; Setiawan, Dena Latif (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the effect of using Kahoot-based instructional media on the learning outcomes of tenth-grade students at SMK Muhammadiyah 2 Kuningan. The research employed a quantitative approach with a quasi-experimental design. Data collection instruments included pretest and posttest assessments to measure learning outcomes, as well as a questionnaire to gather students’ responses toward the use of Kahoot. The study involved 15 students from class X TKJ 1. The findings revealed an increase in the average score from 36.73 on the pretest to 40.07 on the posttest. Normality and homogeneity tests indicated that the data were normally distributed and homogeneous. Furthermore, the Paired Sample t-Test showed a significance value of 0.000 (< 0.05), confirming a statistically significant difference between pretest and posttest scores. This indicates that the use of Kahoot had a positive and significant impact on students' learning achievement. Additionally, questionnaire results demonstrated highly positive student responses, with all items meeting strong validity and excellent reliability standards (Cronbach’s Alpha = 0.999). These results support the idea that interactive learning tools like Kahoot can enhance student motivation, engagement, and understanding during the learning process.